2018
DOI: 10.3389/fphar.2018.01473
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Systems Pharmacology Method to Investigate Molecular Mechanisms of Scutellaria barbata D. Don for Non-small Cell Lung Cancer

Abstract: Non-small cell lung cancer (NSCLC) is the most ordinary type of lung cancer which leads to 1/3 of all cancer deaths. At present, cytotoxic chemotherapy, surgical resection, radiation, and photodynamic therapy are the main strategies for NSCLC treatment. However, NSCLC is relatively resistant to the above therapeutic strategies, resulting in a rather low (20%) 5-year survival rate. Therefore, there is imperative to identify or develop efficient lead compounds for the treatment of NSCLC. Here, we report that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…To directly reflect the relationship between compounds, targets, pathways and diseases, we constructed C-T network and T-P network by Cytoscape 3.7.0 [ 75 ], which is a popular bioinformatics package for biological network visualization and data integration. In the generated network, the nodes represent compounds, targets and pathways, and the interactions between them were represented by edges.…”
Section: Methodsmentioning
confidence: 99%
“…To directly reflect the relationship between compounds, targets, pathways and diseases, we constructed C-T network and T-P network by Cytoscape 3.7.0 [ 75 ], which is a popular bioinformatics package for biological network visualization and data integration. In the generated network, the nodes represent compounds, targets and pathways, and the interactions between them were represented by edges.…”
Section: Methodsmentioning
confidence: 99%
“…We investigated human target genes/proteins that interact with active phytochemical compounds in SMT using the Search Tool for Interactions of Chemicals (STITCH) 5 [65], Similarity Ensemble Approach (SEA) [66], Swis-sTargetPrediction [67,68], and PharmMapper [69]. Computational modeling methods, including systematic drug targeting tool (SysDt) [70] and weighted ensemble similarity (WES) algorithm [71], were also employed for target identification as descried previously [72][73][74][75][76][77][78]. Subsequently, we confirmed detailed information regarding the targets, including their scientific name, relevant gene/protein ID, and organism, and further standardized the targets using Uniprot [79].…”
Section: Investigation Of the Targets Of Active Compounds In Smtmentioning
confidence: 99%
“…To identify the potential therapeutic targets of SMT, we employed an in silico approach to assess the biological interactions between the active phytochemical compounds and human genes/proteins using STITCH 5 [65], SEA [66], SwissTargetPrediction [67,68], and PharmMapper [69]. Computational modeling methods such as SysDt [70] and WES algorithm [71] were also employed for target identification as descried previously [72][73][74][75][76][77][78]. Hence, a total of 230 targets were obtained for the 16 active phytochemical compounds in SMT (Supplementary Table S3).…”
Section: Identification Of the Targets Of Active Phytochemicalmentioning
confidence: 99%
“…Fortunately, systems pharmacology, as a new discipline based on the basic theories of pharmacology and systems biology pharmacology, integrating pharmacology feature mapping, multiple targeting techniques, network pharmacology, and pathway analyses, has gradually become a powerful tool to investigate the therapeutic mechanisms of TCM (Su et al, 2019;Zhou et al, 2019). For example, Liu et al found 33 compounds with potential anticancer effects from Scutellaria barbata D. Don and investigated their mechanisms in treating non-small cell lung cancer by systems pharmacology method (Liu et al, 2018). However, previous systems pharmacology studies usually consider drug-like compounds in herb databases.…”
Section: Introductionmentioning
confidence: 99%